Interrogating the "productive" home gardener in a time of pandemic lockdown in the Philippines. Issue 3 (2nd July 2020) - Montefrio, Marvin Joseph F.
Abstract: Interest in home gardening has burgeoned since governments around the world imposed lockdowns to suppress the spread of SARS-CoV-2. This essay reflects on the growth of home gardens in the locked-down Philippines by analyzing discourses in two home gardening interest groups in Facebook. A particularly salient discourse revolves around the notion of being a "productive" home gardener in a time of pandemic. While the "productive" home gardener discourse appears to be benign and even ideal, overemphasizing it disregards the nuances of class dynamics in home gardening. It also risks idealizing the role of the individual gardener as the solution to the crisis, thereby downplaying the importance of addressing broader structural issues in crisis management and food provisioning. In this essay, the author argues that home gardeners should move beyond the productivity discourse and instead focus on growing communities that are committed to inclusivity, while also acknowledging and supporting other initiatives that target structural issues.